Peran Rumah Budaya Indonesia ( RBI ) di Korea Selatan dalam Mempromosikan Soft Power Indonesia di Tengah Dominasi Hallyu - Mia Kusumawati Ciptaningrum; Arie Kusuma Paksi (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
This study examines the strategic role of the Indonesian Cultural Center (Rumah Budaya Indonesia/RBI) in South Korea in advancing Indonesia’s soft power amid the prevailing dominance of Hallyu. Although bilateral relations between the two countries have been strengthened through a Strategic Partnership since 2006, the imbalance in cultural influence necessitates a planned and sustainable institutional diplomacy mechanism. RBI, initiated by the Ministry of Education and Culture and formally established as the Indonesia Centre at Busan University of Foreign Studies in June 2022, is intended to serve as an official instrument for the implementation of Indonesia’s soft power. This research employs a qualitative single instrumental case study approach, guided by Soft Power and Cultural Diplomacy frameworks. RBI applies two key strategies, namely Direct Diplomacy through physical engagement such as gamelan classes and batik workshops; and Indirect Diplomacy, which leverages online BIPA (Indonesian Language for Foreign Speakers) programs and innovative digital platforms including the AI-based iwearbatik initiative. Findings highlight the effectiveness of RBI in generating heightened public interest in Korea, reflected in the substantial growth of online BIPA learners. This progress contributes significantly to reinforcing Indonesia’s positive image and cultural visibility in the global arena.